The Roman Amphitheater of Lambesis - Batna – is an architectural archaeological study - aid, abdelhak; Amrous , Farida (The Algerian Historical Journal, 2026)
It is important to point out that most of the buildings constructed in Rome were influenced by Greek architecture, and that few have Roman origins. However, we have noticed the emergence of a new architectural pattern that flourished with the end of the Republican era and during the Imperial Era, represented by those buildings known as the terraces, which embraced wrestling and animal confrontation activities among what I have come to call the terrace games. To say the least about this architectural pattern is Roman creativity. It was the result of the necessary adjustment, and when the Romans occupied North Africa they built and built this kind of building in the provinces they occupied. This is because of the great importance they attached to these facilities in their daily lives. As a model of our study, we have chosen the Lambezis Tazoult Batna, which is located in Numidia Province and which we are going to study artificially and architecturally. In this study, we adopted a descriptive approach that described all the structural and architectural components of the Lambezis amphitheater.